Efficient Floating-Point Representation for Balanced Codes for FPGA Devices - Villalba-Moreno, Julio; Hormigo-Aguilar, Javier; Corbera-Peña, Francisco Javier; González, Mario; López-Zapata, Emilio (My University, 2013)
We propose a floating–point representation to deal efficiently with arithmetic operations in codes with a balanced number of additions and multiplications for FPGA devices. The variable shift operation is very slow in these devices. We propose a format that reduces the variable shifter penalty. It is based on a radix–64 representation such that the number of the possible shifts is considerably reduced. Thus, the execution time of the floating–point addition is highly optimized when it is performed in an FPGA device, which compensates for the multiplication penalty when a high radix is used, as experimental results have shown. Consequently, the main problem of previous specific highradix FPGA designs (no speedup for codes with a balanced number of multiplications and additions) is overcome with our proposal. The inherent architecture supporting the new format works with greater bit precision than the corresponding single precision (SP) IEEE–754 standard.
Trabajo premiado con Best paper Award
Keywords: Aritmética computacional; Computer arithmetic